MODEL PENGELOLAAN ZAKAT INFAK SEDEKAH DITINJAU DARI UNDANG-UNDANG NOMOR 23 TAHUN 2011 TENTANG PENGELOLAAN ZAKAT DAN PERATURAN PEMERINTAH NOMOR 14 TAHUN 2014 : (Studi di Masjid Jami' Kota Malang) - Nur Husen, Mohamad (TIJAROTANA : Jurnal Ekonomi Dan Bisnis Syariah, 2020)
Jami 'Malang is one of the important elements in the Malang area which has been carrying out charity, Infaq, Shodaqah (ZIS) with a variety of management. Management of ZIS in Jami 'has a value of its own that is different from other mosques in general, especially in terms of the collection, distribution and utilization. The aims of this research know about how the management of zakat Infaq Shodaqah in Jami Malang. And as for the second aim know, How Shodaqah Infaq zakat management in Jami' Malang in terms of Act No. 23 of 2011 on the management of zakat Article 2 and Rule government No. 14 of 2014 article 56 and 57. This type of research in this study is the kind of empirical research with a qualitative approach. The method of analysis in this research is descriptive method using primary data as the main data obtained directly from the object of research with secondary data supported the Act. The results study is that the model of the management of zakat, Infaq, Shodaqah in Jami 'Malang in ZIS collection can be through three forms namely Masjid accounts, charity boxes, and secretarial. The distribution of zakat is done in the form of weekly, monthly, yearly and proposals. As for the charity Infaq fund management utilized in the form of land use for the production of drinking water and used for the construction and maintenance of mosques which include payment of electricity and facilities. Implementation of management in Jami 'is not contrary to the Act No. 23 of 2011 Article 2 on the principle of zakat management, but not according to Government Regulation No. 14 Year 2014 Article 56 and 57 of the status of the management of the institution.